EDUCATION POLICIES AND TEACHER DEPLOYMENT IN NORTHERN IRELAND: ETHNIC SEPARATION, CULTURAL ENCAPSULATION AND COMMUNITY CROSS-OVER. Issue 2 (3rd March 2020) - Milliken, Matthew; Bates, Jessica; Smith, Alan
ABSTRACT: Education is a key mechanism for the restoration of inter-community relations in post-conflict societies. The Northern Ireland school system remains divided along sectarian lines. Much research has been conducted into the efficacy of initiatives developed to bring children together across this divide but there has been an absence of studies into the impact of educational division on teachers. A number of policies, separately and in combination, restrict teachers' options to move across and between the divided school sectors. The recruitment of teachers is excepted from fair employment legislation; details of teachers' community identity are consequently not collected, and little is known about the impact that ethnic identity, educational policies and sectoral practices have had on teacher deployment. This quantitative project investigates the extent to which the deployment of teachers in mainstream schools in Northern Ireland reflects the enduring community divide. It is observed that, whilst primary schools are staffed mainly by community-consistent teachers, there has been an increase in cross-over teachers in post-primary schools – particularly in the grammar sector. Around one-in-five teachers have had no educational experience outside of their community of origin; this cultural encapsulation may contribute to a reluctance to engage with contentious issues in reconciliation programmes.